Das internationale Investitionsregime zwischen Reform und Revolution - Krajewski, Markus; Hoffmann, Rhea (Kölner Schrift zum Wirtschaftsrecht, 2016)

International investment law, democratic legitimacy, and the protection of human rights: Transforming constitutional property protection - Hoffmann, Rhea (International Investment Protection and Constitutional Law, 2022)
CRIS-Team Scopus Importer:2024-12-16

Introduction to the Research Handbook on Foreign Direct Investment - Krajewski, Markus; Hoffmann, Rhea (Edward Elgar Publishing Ltd., 2019)
CRIS-Team Scopus Importer:2023-03-21

Research Handbook on Foreign Direct Investment - Krajewski, Markus; Hoffmann, Rhea (Edward Elgar Publishing Ltd., 2019)
Increasing international investment, the proliferation of international investment agreements, domestic legislation, and investor-State contracts have contributed to the development of a new field of international law that defines obligations between host states and foreign investors with investor-State dispute settlement. This involves not only vast sums, but also a panoply of rights, duties, and shifting objectives at the juncture of national and international law and policy. This engaging Research Handbook provides an authoritative account of these diverse investment law issues.
CRIS-Team Scopus Importer:2023-03-21

Staatsschuldenkrise im Euro-Raum und die Austeritätsprogramme von IWF und EU - Krajewski, Markus; Hoffmann, Rhea (Kritische Justiz, 2012)